Case Report: Allograft aortic valve replacement in irreparable infant mitral valve - Niu, Yuqing; Cheng, Shaoxian; Dong, Nianguo; Zhou, Cheng (Frontiers in Cardiovascular Medicine, 2024)
This case report describes a 3-month-old male infant diagnosed with severe mitral stenosis (MS) and mitral regurgitation (MR) by transthoracic echocardiography. The male infant initially underwent complex mitral valve repair surgery. However, postoperative deterioration occurred with hemodynamic instability and shock, necessitating multiple resuscitation efforts and ultimately requiring support from Extracorporeal Membrane Oxygenation (ECMO). Given the serious conditions, the cardiac team decided to perform mitral valve replacement with a fresh allograft aortic valve. Postoperatively, the patient was promptly weaned off ECMO support, and the valve demonstrated sustained functionality throughout the long-term follow-up.